WISATA BUDAYA DALAM TRADISI TENUN DI KECAMATAN MEMPURA KABUPATEN SIAK - Maulia, Rafita; Sidiqi, rafita_maulia@yahoo.com Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to see cultural tourism in the tradition of weafing in kecamatan mempura kabupaten siak, tradition of weafing is tradition inherited. This research uses the method of deskriptif kualitatif. The key informant in this research is chaiman of the joint venture group. Whwre as the techniqueof gathering data in this research using interviews and documentations. This research use the theory that in adoption of pengantar ilmu pariwisata (pitana and diarta 2009). The results showed cultural tourism in the tradition of weaving is very much, traveler gat an education, knowledge, experience, and cultural uniqueness in tradition of weaving. Keywords : Cultural Tourism, Tradition, Cultural Tourism In The Tradition Of Weaving In Kecamatan Mempura Kabupaten Siak.